The use of diode lasers in non-surgical therapy of periodontitis - Małgorzata Majka Kulińska - Michalska; Natalia Lewkowicz; Natalia Ćwiklińska; Magda Lisiecka; Patrycja Czaplicka-Szydlik (Journal of Pre-Clinical and Clinical Research, 2020)
Introduction Periodontitis is a disease of multifactorial etiology and complex clinical manifestation. Removal of subgingival bacterial biofilm is a fundamental procedure in the treatment of periodontitis. Scaling and root planing (SRP) is currently the gold standard in the treatment of periodontitis, but in some cases such a procedure does not provide satisfactory results. The use of lasers in the treatment of periodontitis is one of the alternative adjunctive methods that has recently become more popular.